Looking Beyond September 11 - Saeed A. Khan (American Journal of Islam and Society, 2012)
The Fortieth Annual AMSS (Association of Muslim Social Scientists of North America) Conference, held at John Jay College at the City University of New York in New York City, marked a decade since September 11 by reviewing the past ten years of the Muslim narrative, with particular focus on the past year and the considerable social and political changes in the Middle East and North Africa. Welcomed by John Jay College Provost and Senior Vice President for Academic Affairs, Dr. Jane Bowers, and by outgoing AMSS President Dr. Ali Mazrui ‒ the conference’s one-day format ensured an intensive and stimulating session, which captured the energy of the participants and attendees that filled the symposium. While a four-panel conference featuring only twelve presenters may appear small in comparison to some academic meetings, AMSS again proved that quality eclipsed quantity in offering a diverse, yet deep analysis of contemporary issues ‒ ranging from the Arab Spring to domestic discourses highlighting and targeting Muslims. A panel entitled, “The Arab Spring: Paths to Democracy in the Middle East and North Africa,” opened the day’s proceedings by assessing the very fluid and evolving situation in the heart of the Arab world. Khalid Madhi (Adjunct Professor at St. Xavier University and PhD Student Research and Teaching Assistant at the University of Illinois at Chicago) focused on how the transformative movements in Tunisia and Egypt would be felt in Morocco by offering a study of the country’s Islamist efforts. Umar Oseni (Visiting Fellow at the Islamic Legal Studies Program at the Harvard Law School and Post-doctoral Scholar and Lecturer at the International Islamic University Malaysia) shifted the discussion from a specific country to a more regional approach when he proposed a model for conflict management that is inherent within Islam itself. Finally, Mohamed Nimer (Assistant Professor of International Relations at the School of International ...